The Psychological Effects of Short-Term Fasting in Healthy Women - Watkins, Ellen; Serpell, Lucy (Frontiers in Nutrition, 2016)
Objective: The study aimed to investigate affective responses to 18-hour fasting in healthy controls. In particular the study focused on self-reported mood, irritability, sense of achievement, reward, pride, and control. Method: Participants were a non-clinical sample of 52 women with a mean age of 25. A repeated-measures design was used, whereby participants provided diary measures of psychological variables throughout both 18-hour fasting and non-fasting periods. Results: Fasting led to increased irritability, and also to positive affective experiences of increased sense of achievement, reward, pride, and control. Discussion: Even short-term fasting in healthy controls can lead to positive psychological experiences. This lends support to cognitive-behavioural and cognitive-interpersonal models of ANR, which suggest that dietary restriction is maintained through positive reinforcement.